2010
DOI: 10.1080/19942060.2010.11015337
|View full text |Cite
|
Sign up to set email alerts
|

Variable Turbulent Schmidt and Prandtl Number Modeling

Abstract: This paper describes variable turbulent Schmidt and Prandtl number formulations, based on Rodi's (1980) algebraic Reynolds stress model adapted to velocity-scalar correlations. Since the approach is algebraic in nature, it does not introduce transport equations beyond the ones already existing to compute the flow, rendering it a viable engineering tool. The method is scrutinized against several test cases, including a 3D Scramjet combustor problem. Results are encouraging and lend confidence in the proposed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Goldberg et al [70] proposed an approach based on an extension of the [20] algebraic Reynolds stress model and relies on Reynolds stresses' anisotropy. The approach used these stresses to algebraically build velocity-scalar correlations, which were the starting point for a variable Sc t formulation.…”
Section: Environmental Flow Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goldberg et al [70] proposed an approach based on an extension of the [20] algebraic Reynolds stress model and relies on Reynolds stresses' anisotropy. The approach used these stresses to algebraically build velocity-scalar correlations, which were the starting point for a variable Sc t formulation.…”
Section: Environmental Flow Commentsmentioning
confidence: 99%
“…A second group of studies investigated the question if Sct is a constant or it is varying inside the flow domain [66,[70][71][72]. Koeltzsch [66] carried out wind tunnel experiments in a turbulent boundary layer above a flat plate.…”
Section: Contaminant Dispersion Due To Transverse Turbulent Mixing Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A variable Pr T model proposed by Xiao et al (2007) is found to improve SBLI results. Similar models are proposed by Sommer, So & Zhang (1993), Brinckman, Calhoon & Dash (2007) and Goldberg et al (2010). In another work, Bowersox (2009) presents the exact transport equation for the turbulent energy flux, and simplifies it to get an algebraic model in terms of gradients in mean quantities.…”
Section: Introductionmentioning
confidence: 88%
“…For turbulent flows, the mass diffusion is influenced mostly by the turbulent transport. This is determined by the turbulent Schmidt number, and measures the ratio of momentum and mass diffusivity (Goldberg, Palaniswamy, Batten, & Gupta, 2010;Reynolds, 1975;Tominaga & Stathopoulos, 2007;Yeung, Xu, & Sreenivasan, 2002). The turbulent Schmidt number is relatively insensitive to the molecular fluid properties, thus there is little reason to alter the default value of Sc t = 0.7 for any species (ANSYS R Fluent R , 2012).…”
Section: Species Transportmentioning
confidence: 99%